Effects of the RH-40 Cremophor Concentration on the Formulation of the Vaccinium varingiifolium (Blume) Miq leaf Extract Nanoemulsion - Yulius Evan Christian; Deni Rahmat; Yunahara Farida (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2023)
Cantigi (Vaccinium varingiaefolium (Blume) Miq.) contains anthocyanins, chlorophyll, phenols, saponins, steroids, tannins, triterpenoids, flavonoids, and antioxidant activity. This study aimed to obtain the concentration of cremophor RH-40 as an optimal and stable surfactant during storage in Cantigi leaf extract nanoemulsion formulation process. Cantigi leaf extract was made by kinetic maceration in stages with n-hexane, ethyl acetate, and 96% ethanol as solvent, then evaporated with an evaporator. The extract was tested for solubility using various solvents before making the nanoemulsion. Nanoemulsions were prepared by varying the amount of cremophor RH-40 in three formulas (5%, 7.5%, and 10%) with stirring at 400 rpm at 40 Â°C. The nanoemulsions were characterized by particle size, zeta potential, and storage for 5 days. The evaluation results of Formula 1, 2, and 3 have an average particle size of 224.7, 226.5, and 198.3 nm, with a polydispersity index of 0.565, 0.237, and 0.223. The zeta potential values are - 43.7, - 39.2, and - 42.3 mV, respectively. The results of the storage of nanoemulsions for 5 days showed that in formulas 1 and 2 a precipitate formed, while in formula 3, there was no precipitate. Based on the optimization results obtained, cremophor RH-40 10% obtained a stable nanoemulsion that does not occur with no observed sedimentation/precipitation during storage.